Estudio de factibilidad para la creación de una empresa comercializadora de dispositivos intercomunicadores adaptándolos a los cascos de motociclistas – “Adecascos”, en Manizales- Caldas (2013)
ADECASCOS The project is a feasibility study for the creation of a company, in the city of Manizales Caldas, responsible for marketing and adaptation of intercoms on helmets for motorcyclists, which was developed in order to increase comfort and comfort movements they perform. For feasibility in creating this company were determined following objectives which opportunity provides the market town of Manizales, technical processes and elements, which system is most suitable organizational, what is the feasibility Colombian law provides for its establishment and operation. Inductive research method. Type descriptive study and research. In the methodology, surveys motorcycle owners whose tabulation and results obtained were satisfactory and gave rise to determine the feasibility of this project. The scope of this study is to motorcyclists with a new product, intercom device adapted to helmets for motorcyclists (driver and barbecue) allowed comfortable and fluent communication, and at an affordable price, and that for the product acquisition is an importer has provided good costs, which can create marketing strategies for market positioning of the city of Manizales. In conclusion this project is financially viable and can be taken as a life project.